2021
DOI: 10.1144/qjegh2021-005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three methods to assess natural source zone depletion at paved fuel retail sites

Abstract: Natural Source Zone Depletion (NSZD) encompasses all processes that result in petroleum hydrocarbon light non-aqueous phase liquid (LNAPL) mass loss. Vertical gas transport between the subsurface and atmosphere is a key component of NSZD. Gas exchange with the atmosphere may be restricted at sites with ground cover which is typical for European fuel retail sites. This raises questions of whether, and to what extent, the generic NSZD conceptual model applies at these sites. Here, we present a study that evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…All A–C soil gas profiles displayed more apparent O 2 usage and CO 2 and CH 4 production in the deeper subsurface. The concentrations of VOCs were about 2 to 4 orders lower than CO 2 and CH 4 , which suggested that nonmethane hydrocarbon contaminants were scarcely depleted through volatilization, but were rather potentially biodegraded by functional microorganisms in the source zone, consistent with previous studies [ 4 , 13 , 14 , 15 , 16 , 17 , 19 ]. For the background (uncontaminated) samples, no VOCs and CH 4 were generated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All A–C soil gas profiles displayed more apparent O 2 usage and CO 2 and CH 4 production in the deeper subsurface. The concentrations of VOCs were about 2 to 4 orders lower than CO 2 and CH 4 , which suggested that nonmethane hydrocarbon contaminants were scarcely depleted through volatilization, but were rather potentially biodegraded by functional microorganisms in the source zone, consistent with previous studies [ 4 , 13 , 14 , 15 , 16 , 17 , 19 ]. For the background (uncontaminated) samples, no VOCs and CH 4 were generated.…”
Section: Discussionsupporting
confidence: 90%
“…Gradient methods were then used to estimate NSZD rates in various LNAPL-contaminated sites, including crude oil, diesel, jet fuel, and gas condensate, etc. [ 4 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This, however, cannot be done for the monitoring well analysis as only a single depth is available at the base of the vadose zone. Recently, Smith et al (2020) have shown that a second soil‐gas sample can be collected in monitoring wells at the top of the screened interval to apply the gradient method. We did not do this and decided to determine if a gradient could be estimated from the shallow soil‐gas measurements as not all monitoring wells are screened at shallow depths.…”
Section: Discussionmentioning
confidence: 99%
“…According to a large number of field case data [ 1 , 3 , 5 , 11 , 12 , 20 , 29 , 36 ], there are generally two situations in the profile gas concentration. One is that, within a considerable depth range from the surface to the contaminated source area, oxygen and carbon dioxide have a constant concentration gradient, and methane is almost non-existent within this range.…”
Section: Discussionmentioning
confidence: 99%
“…The methods currently used to assess NSZD rates of petroleum hydrocarbon-contaminated sites mainly rely on subsurface gas fluxes and thermal fluxes associated with natural degradation processes [ 10 ]. Commonly used methods include the gas concentration gradient method, dynamic chamber method, carbon capture method, and thermodynamic gradient method [ 10 , 11 , 12 ]. Many studies have used different methods to evaluate the natural attenuation of contaminated sites, even making improvements and corrections to these methods [ 10 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%